PENGELOLAAN SARANA DAN PRASARANA PENDIDIKAN DI SMK - Ramlan Susanto; Rohiat Rohiat; Puspa Djuwita (Manajer Pendididikan, 2017)
The purpose of this study was to find out what activities are carried out in vocational High School Education Number three South Bengkulu manage educational facilities and infrastructure of the school, ranging from planning, procurement, maintenance, inventory, and remove the facilities and infrastructure in schools. In conducting this study, researchers used a qualitative descriptive method. Data for this study were collected through a series of observation, interviews and documentation. The study concluded that vocational secondary schools number three South Bengkulu has been managing the facilities and infrastructure in accordance with the principles of management in general. Elimination of the educational facilities formed on procedures considered complicated and afraid to risk.